Exhaustion of T cells after renal transplantation - Wang, Xiujia; Zhang, Jinghui; Zhong, Pingshan; Wei, Xiuwang (Frontiers in Immunology, 2024)
Renal transplantation is a life-saving treatment for patients with end-stage renal disease. However, the challenge of transplant rejection and the complications associated with immunosuppressants necessitates a deeper understanding of the underlying immune mechanisms. T cell exhaustion, a state characterized by impaired effector functions and sustained expression of inhibitory receptors, plays a dual role in renal transplantation. While moderate T cell exhaustion can aid in graft acceptance by regulating alloreactive T cell responses, excessive exhaustion may impair the recipient’s ability to control viral infections and tumors, posing significant health risks. Moreover, drugs targeting T cell exhaustion to promote graft tolerance and using immune checkpoint inhibitors for cancer treatment in transplant recipients are areas deserving of further attention and research. This review aims to provide a comprehensive understanding of the changes in T cell exhaustion levels after renal transplantation and their implications for graft survival and patient outcomes. We discuss the molecular mechanisms underlying T cell exhaustion, the role of specific exhaustion markers, the potential impact of immunosuppressive therapies, and the pharmaceutical intervention on T cell exhaustion levels. Additionally, we demonstrate the potential to modulate T cell exhaustion favorably, enhancing graft survival. Future research should focus on the distinctions of T cell exhaustion across different immune states and subsets, as well as the interactions between exhausted T cells and other immune cells. Understanding these dynamics is crucial for optimizing transplant outcomes and ensuring long-term graft survival while maintaining immune competence.